Sosialisasi Mengenalkan Pola Hidup Sehat Sejak Dini Melalui Pendidikan Jasmani - Sri Wahyuningsi Laiya; Sulastya Ningsih; Nurul Aini Mm Sodik; Sri Ramla Wati Monoarfa (FKIP, Universitas Palangka Raya, 2025)
A healthy lifestyle is an important foundation in achieving a good quality of life. Physical education in schools plays a significant role in introducing and instilling healthy living habits in children from an early age. In addition, the role of parents as primary educators at home is crucial in supporting and strengthening healthy habits taught in schools. Collaboration between physical education and education from parents can create a conducive environment for children to adopt a healthy lifestyle sustainably. This activity was carried out in Timbuolo Village, Botupingge District, Bone Bolango Regency, and attended by the village head, teachers, principals, and parents. Through this Community Service socialization activity, it is hoped that parents can increase their insight into Health and a healthy lifestyle so that children can develop according to their developmental stages